2020
DOI: 10.1007/s11469-020-00331-y
|View full text |Cite
|
Sign up to set email alerts
|

Fear of COVID-19 and Positivity: Mediating Role of Intolerance of Uncertainty, Depression, Anxiety, and Stress

Abstract: This study aimed to investigate the mediating role of intolerance of uncertainty, depression, anxiety, and stress in the relationship between the fear of COVID-19 and positivity. The partici-pantsconsistedof960individuals,including663females(69.1%)and297males(30.9%).Theage oftheparticipantsrangedbetween18and76(29.74 ± 9.64).Asaresultofthecorrelationanalysis,a positive relationship was found between fear of COVID-19 and intolerance of uncertainty, depression, anxiety, and stress, and a negative relationship was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

83
510
11
61

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 677 publications
(665 citation statements)
references
References 35 publications
83
510
11
61
Order By: Relevance
“…In accordance with the main hypothesis, fear of COVID-19 and perceived stress mediated in the relationship between self-blame regret and depression. In line with this hypothesis, previous studies reported that fear of COVID-19 in ates perceived stress (Bakioğlu, Korkmaz & Ercan, 2020); perceived stress (e.g., Zhang, Peters & Chen, 2018) and particularly pandemic related stress contributes to elevated levels of depressive symptoms (Montano & Acebes, 2020). Taking together, within the framework of all discussed ndings, it can be concluded that self-blame regret impacts in depression through fear of COVID-19 and psychological stress.…”
Section: Discussionsupporting
confidence: 64%
“…In accordance with the main hypothesis, fear of COVID-19 and perceived stress mediated in the relationship between self-blame regret and depression. In line with this hypothesis, previous studies reported that fear of COVID-19 in ates perceived stress (Bakioğlu, Korkmaz & Ercan, 2020); perceived stress (e.g., Zhang, Peters & Chen, 2018) and particularly pandemic related stress contributes to elevated levels of depressive symptoms (Montano & Acebes, 2020). Taking together, within the framework of all discussed ndings, it can be concluded that self-blame regret impacts in depression through fear of COVID-19 and psychological stress.…”
Section: Discussionsupporting
confidence: 64%
“…In relation to anxious-depressive symptoms, being older was significantly negatively related with depression and anxiety, as in the study by Gonzalez-Sanguino et al (2020), with women exhibiting higher scores in anxiousdepressive symptoms both in their study and ours. Regarding fear of COVID-19, previous studies have highlighted the difference between sexes, with fear being significantly higher in women (Bakioglu, Korkmaz & Ercan, 2020). Additionally, in the study by Castillejos et al (2020), an association was found between lower age and higher suicidal ideation scores.…”
Section: Resultsmentioning
confidence: 70%
“… 43 Contrarily, correlations between anxiety and place of residence, level of education or having relatives infected with SARS-CoV-2 were not observed in some studies. 44 In our study, media habits were indirectly studied in the FCV-19S, however, it is difficult to measure the media habits in an objective manner. 43 Not assessing the above-mentioned factors has to be considered as a limitation of our study.…”
Section: Discussionmentioning
confidence: 95%